2015
DOI: 10.1103/physreva.92.012320
|View full text |Cite
|
Sign up to set email alerts
|

Tunable coupler for superconducting Xmon qubits: Perturbative nonlinear model

Abstract: We study a recently demonstrated design for a high-performance tunable coupler suitable for superconducting Xmon and planar transmon qubits [Y. Chen et al., arXiv:1402.7367]. The coupler circuit uses a single flux-biased Josephson junction and acts as a tunable current divider. We calculate the effective qubit-qubit interaction Hamiltonian by treating the nonlinearity of the qubit and coupler junctions perturbatively. We find that the qubit nonlinearity has two principal effects: The first is to suppress the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 28 publications
0
75
1
Order By: Relevance
“…In a superconducting device, the qubits are built with a Josephson tunnel element, an inductance and a capacitor, 11 whereas local operations and measurements are performed by coupling the qubit to a resonator. 12 The interactions can be designed using lithographic techniques by jointly coupling two qubits via a capacitor 13 or an inductance, 14 and can be modelled via an effective two-body Hamiltonian P α J α σ α σ α 15,16 where σ α are the Pauli matrices. Because of the flexibility in wiring the pairwise interactions among the qubits, it is possible to arrange them in a planar graph structure, namely a collection of vertices and links, in which the vertices correspond to the qubits and the links correspond to the two-body interactions between them.…”
Section: Introductionmentioning
confidence: 99%
“…In a superconducting device, the qubits are built with a Josephson tunnel element, an inductance and a capacitor, 11 whereas local operations and measurements are performed by coupling the qubit to a resonator. 12 The interactions can be designed using lithographic techniques by jointly coupling two qubits via a capacitor 13 or an inductance, 14 and can be modelled via an effective two-body Hamiltonian P α J α σ α σ α 15,16 where σ α are the Pauli matrices. Because of the flexibility in wiring the pairwise interactions among the qubits, it is possible to arrange them in a planar graph structure, namely a collection of vertices and links, in which the vertices correspond to the qubits and the links correspond to the two-body interactions between them.…”
Section: Introductionmentioning
confidence: 99%
“…A local optimization algorithm is then carried out for a corresponding reduced set of parameters; see discussion in the text. It is worth noting that the majority of the network is made up of ZZ interactions, which is obtainable in superconducting circuits, among others, as shown by Geller et al [47]. Additionally, McKay et al showed that it was possible to obtain (XX + Y Y ) interactions in a superconducting circuit [48], lending itself nicely for the interactions between the second and third qubits of this network.…”
Section: Resultsmentioning
confidence: 85%
“…However, their coupling is determined by the fixed geometric arrangement of the resonators, resulting in a static coupling g bs that can not be switched off. In order to make the coupling switchable, different schemes have been proposed theoretically [23,24] and implemented experimentally [13][14][15]. All these proposals are based on superconducting rings acting as tunable couplers (cf.…”
Section: Boson Sampling With Superconducting Circuitsmentioning
confidence: 99%